Determinan Pembiayaan Musyarakah Pada Perbankan Syariah Di Indonesia - Teguh Permana; Andriani Puspitaningsih (Universitas Siliwangi, 2020)
The results showed that third party funds, profit sharing rates, and problematic financing had a significant effect on musharaka financing, while inflation was not significant. Third party funds have a positive effect, while the profit sharing rate and problematic financing have a negative effect on musyarakah financing. Research also shows that there are different interceptions between BUS / UUS and BPRS where the BPRS intercept is greater than the BUS / UUS intercept. This shows that BPRS are more attractive to the public than BUS / UUS. The findings of this study imply that to increase the capacity of musharaka financing, efforts to increase community savings in third party funds are needed, promote a fair / appropriate profit sharing rate, and control problematic financing.Keywords: musharaka, dpk, profit sharing, financing problems, inflation.